Toward enhanced competence acquisition in clinical practice: implementing blended learning for physical therapy students - Bermejo-Franco, Alberto; García-Arrabé, María; Díaz-Meco-Conde, Raquel; González-Fernández, Laura; Ruiz-Ruiz, Beatriz; del Prado-Álvarez, Rebeca; Aladro-Gonzalvo, Arian Ramón (Frontiers in Education, 2024)
BACKGROUND: The COVID-19 closure necessitated curricular changes, impacting educational activities, teaching methods, and assessment systems, particularly in curricular practices. However, the effects of these adaptations on acquiring competencies in the clinical context remain insufficiently explored. OBJECTIVE: This study aims to assess the potential impact of curricular adaptations during the COVID-19 lockdown on the expected learning outcomes in the Basic Manual Therapy course. Our focus is on competencies within the clinical domain, encompassing clinical practice, medical history, and reflective journaling during clinical practices. We aim to compare these experiences with students who underwent no adaptations in the previous academic year. METHODS: This retrospective cohort study, aligned with STROBE guidelines, examines physical therapy university students. Students are categorized into two groups based on enrollment timing: the 'non-exposed group' (NE) completed the Basic Manual Therapy course in 2018-2019 and Clinical Stays I in 2019-2020, while the 'exposed group' (E) finished the Basic Manual Therapy course in 2019-2020 and participated in Clinical Stays I during 2020-2021. RESULTS: Of 282 included students, the curricular adaptations for Basic Manual Therapy [U(E Mdn=7.7000, NE Mdn=7.7000)= 9286, z=-0.546, p=.585] and Clinical Stays I [U(E Mdn=8.5900, NE Mdn=8.4700)= 9600, z=-0.078, p=.938] showed no statistically significant impact on competencies and learning outcomes when comparing the two groups. Notable differences were observed in reflective journaling marks [U(E Mdn =8.300, NE Mdn=8.000)= 7770.5, z=-2.796, p=.005] and the Student Progress item in Reflective Journaling [U(E Mdn=9.000, NE Mdn=8.000)= 7216.5, z=-3,668, p=.000], favoring the E cohort. Both groups showed a low, positive correlation between the ordinary BMT mark and the ordinary CS I mark [Rho (E =.206, NE =.170), p< 0.05]. CONCLUSION: Despite study limitations, findings emphasize that non-face-to-face curricular adjustments during the COVID-19 pandemic effectively prevented negative impacts on clinical skills acquisition. Activities in the Basic Manual Therapy subject facilitated positive skill development in Clinical Practice, contributing to favorable learning outcomes, particularly in Clinical History and Reflective Journaling formulation.